Experiences of HIVda: intervention with and from HIV-positive people in Yucatan, Mexico - Puc-Vázquez, Eduardo David (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
The condition of seropositivity implies a new beginning for people because a splitting of their person is presented and they require a reconstruction of their life. At the social level, life deconstruction can be characterized by the absence of power and the presence of social stigma, which can impact the affectivity and community participation of people living with HIV (PLHIV). This systematization work aims to reconstruct the process of an intervention carried out from the Participatory Action Research (PAR), for which the Theory of Social Representations was taken up, to approach the socio-affective components of a group of PLHIV and their relationship with stigma and community participation. It was found that affectivity represents an important aspect, being the diagnosis a central aspect in the modification of their meanings and life practices, with a tendency towards isolation and low social participation. Through the intervention, the participants assumed themselves as agents of change, resulting in a break with the stigma of HIV/AIDS, both within the group and with the community. It can be concluded that building participatory processes from affectivity can lead to the re-knowledge and empowerment of their strengths.